Ethno-national basis of russian aggression in the context of global security: a biopolitical approach - Kravets, Anastasia (My University, 2024)
The biopolitical approach to the analysis of aggression allows us to analyze one of the causes of the biggest conflict in Europe after the Second World War. The purpose of the analysis was to draw attention to the ethno-national basis of aggression as a global threat to the existence of humanity, stability, and security in the modern world. The unprovoked aggression of the Russian Federation against the sovereign country of Ukraine has a pronounced ethno-national basis based on the idea of ethnocentrism.
Keywords: : ethnocentrism; aggression; genocide; war; global security